Aleatory Construction Based on Jamming: Stability Through Self‐Confinement. (July 2017) - Murphy, Kieran; Roth, Leah; Peterman, Dan; Jaeger, Heinrich
Abstract : The physical process of jamming could take architectural sustainability/recyclability to a whole new level. It involves achieving structural rigidity through the crowding of particles within a confined space, rather than by permanent bonding. Project Z‐Form, a collaboration between a team of physicists from the JaegerLab at the University of Chicago – including PhD students Kieran Murphy and Leah Roth and professor Heinrich Jaeger – and artist Dan Peterman, sets out to develop a pourable material that not only self‐supports but can also bear loads. Here they explain the project and the concepts behind it.